Hyperplastic Dental Follicle: A Case Report and Literature Review - Ligia Buloto Schmitd; Diego Maurício Bravo-Calderón; Cleverson Teixeira Soares; Denise Tostes Oliveira (Case Reports in Dentistry)
Hyperplastic dental follicle is an odontogenic hamartomatous lesion associated with delayed or tooth eruption failure in young patients. The occurrence of this pericoronal dental lesion may be single or multiple and it seems to be more frequent than literature has reported. We present a literature review focusing on the etiopathogenesis and clinicopathological features of this hamartomatous lesion in young patients. In addition, we reported a case of hyperplastic dental follicle causing delayed tooth eruption of 14-year-old male patient. Microscopic analyses based on routine staining and immunohistochemistry were used to discuss the cells found in pericoronal follicle. This paper reinforces the importance of association between clinical history and radiographic features with microscopic pericoronal follicle examination for diagnosis of this hamartomatous lesion.